CHARACTERISTICS OF CURRENT IN THE SOUTH CHINA SEA VIA ANALYSIS OF THE CURRENT DATA MEASURED IN THE PAST - Xuan, Nguyen Ba; Tuan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2006)
CHARACTERISTICS OF CURRENT IN THE SOUTH CHINA SEA VIA ANALYSIS OF THE CURRENT DATA MEASURED IN THE PAST